2014
DOI: 10.1093/ejcts/ezu385
|View full text |Cite
|
Sign up to set email alerts
|

Development of a next-generation tissue valve using a glutaraldehyde-fixed porcine aortic valve treated with decellularization, α-galactosidase, space filler, organic solvent and detoxification

Abstract: We developed a next-generation α-Gal-free tissue valve with simultaneous use of multiple anticalcification therapies and novel tissue treatments such as decellularization, immunological modification with α-galactosidase, space filler, an organic solvent and detoxification. Future investigations should evaluate α-Gal-free substitutes such as our tissue valve, and a future clinical study is warranted based on these promising preclinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…We did not find significant differences in the concentration of cytokines in our population according to the type of valve implanted even when the valve prostheses are manufactured with different materials. Biological valvular prostheses are made from animal tissue that is subjected to a decellularization process and glutaraldehyde fixation in order to reduce their immunogenicity [19, 20]. The artificial valves are manufactured from various synthetic materials, including carbon graphite, pyrolytic carbon and titanium [21].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find significant differences in the concentration of cytokines in our population according to the type of valve implanted even when the valve prostheses are manufactured with different materials. Biological valvular prostheses are made from animal tissue that is subjected to a decellularization process and glutaraldehyde fixation in order to reduce their immunogenicity [19, 20]. The artificial valves are manufactured from various synthetic materials, including carbon graphite, pyrolytic carbon and titanium [21].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Only the very avant-garde centers, such as the Hannover and Seoul Group, are trying to tackle this important question by means of detergent-based decellularization procedures 13,14 or by using alpha-galactosidase. 15 Tissueengineering research is ongoing in most academic centers of relevance, but commercial producers must instigate the manufacture of such ''humanized'' bioprostheses with potentially longer life spans. The first successful endeavors in that direction have been reported.…”
Section: When Meat Allergy Meets Cardiac Surgery: a Driver For Humanimentioning
confidence: 99%
“…13 As a first step, recent studies demonstrated equivalent physical properties of a-gal-deficient pericardium. 14,15 The main benefit to CRISPR is the ability to perform multiple genetic manipulations simply and efficiently. Of course, a-gal is not the only immunogenic carbohydrate antigen present in bioprosthetic heart valves, and the next generation of valves should address them all.…”
Section: Mammalian Meat Allergy and Advances In Bioprosthetic Valve Tmentioning
confidence: 99%
“…Many researchers decellularize via immersion 47,48 or perfusion 49,50 of the valve, with each methodology adequately removing cellular content. Numerous combinations of detergents and biological agents have been used with varying efficacy, including SDS 47,48,5153 , trypsin 47,5456 , EDTA 47,48,5356 , Triton X-100 47,5053 , sodium deoxycholate 53,54 , DNase/RNase 47,48 , and hypo/hypertonic solutions 48,50 . Some decellularized valves showed immunogenicity and thrombogenicity 54,55 while other valves did not show any immune response 52,57,58 , the discrepancy of which was dependent on not only the decellularization technique but also postprocessing (e.g.…”
Section: Tissue Engineered Heart Valvesmentioning
confidence: 99%